Evaluation of an I-box wind tunnel model for assessment of behavioral responses of blow flies - Moophayak K. (2014)
The behavioral response of flies to olfactory cues remains the focus of many investigations, and wind tunnels have sometimes been employed for assessment of this variable in the laboratory. In this study, our aim was to design, construct, and operate a new model of I-box wind tunnel with improved efficacy, highlighting the use of a new wind tunnel model to investigate the behavioral response of the medically important blow fly, Chrysomya megacephala (Fabricius). The I-box dual-choice wind tunnel designed for this study consists of seven conjoined compartments that resulted in a linear apparatus with clear glass tunnel of 30 × 30 × 190 cm ended both sides with wooden "fan compartments" which are equipped with adjustable fans as wind source. The clear glass tunnel consisted of two "stimulus compartments" with either presence or absence (control) of bait; two "trap compartments" where flies were attracted and allowed to reside; and one central "release compartment" where flies were introduced. Wind tunnel experiments were carried out in a temperature-controlled room, with a room light as a light source and a room-ventilated fan as odor-remover from tunnel out. Evaluation of testing parameters revealed that the highest attractive index was achieved with the use of 300 g of 1-day tainted pork scrap (pork meat mixed with offal) as bait in wind tunnel settings wind speed of 0.58 m/s, during 1.00-5.00 pm with light intensity of 341.33 lux from vertical light and 135.93 lux from horizontal light for testing a group of 60 flies. In addition, no significant response of well-fed and 24 h staved flies to this bait under these conditions was found. Results of this study supported this new wind tunnel model as a suitable apparatus for investigation of behavioral response of blow flies to bait chemical cues in the laboratory. © 2013 Springer-Verlag Berlin Heidelberg.